A Comparison between the Western Understanding of Logos and the Asian Understanding of Dao - Wang, Shu (Transactions on Social Science, Education and Humanities Research, 2024)
The comparative study of Logos in the West and Dao in China has never stopped in academic circles. In a sense, Heraclitus’ Logos and Laozi’s Dao, which came into being in the same axial era, can be regarded as the starting point of Chinese and western philosophy respectively. They are similar in meaning, both of which are constant and contain Dialectic, But whether viewed from the perspective of ontology or epistemology, the differences between them are extremely obvious. This paper intends to make a comparison between Dao and Logos from the different aspects of Chinese and Western ontology, and point out the differences between them from the purpose and way of cognition, as well as the value orientation and development path in the process of cognition. Clarifying this problem will not only help us to deepen our understanding of Logos and Dao, but also help the academic community to deeply explore why the starting points of Chinese and Western philosophy are very similar but have completely different cultural paths.